New records and new species of Magelonidae (Polychaeta) from the Arabian Peninsula, with a re–description of Magelona pacifica and a discussion on the magelonid buccal region - Mortimer, Kate; Cassà, Susanna; Martin, Daniel; Gil, João (Zootaxa, 2012)
Five Magelona species, M. cornuta, M. crenulifrons, M. obockensis, M. pulchella, and an undescribed species (identifiedby Louis Amoureux as M. cornuta in 1983 and described herein as M. montera sp. nov.) have been previously reportedfrom the seas surrounding the Arabian Peninsula. The present study details a further six Magelona species off the coastsof Iran and Qatar, collected between 1998 and 2007. Five species are newly recorded for the region: Magelona cf. agoen-sis, Magelona cf. cincta, M. conversa, Magelona cf. falcifera and M. symmetrica, and one species (M. sinbadi sp. nov.)is deemed new to science. A key is provided for the 15 species with verified reports currently known from the westernIndian Ocean region. Magelona pacifica originally described from Panamá is discussed and re-described due to its simi-larity to M. montera sp. nov. A ‘buccal organ/tube’ in addition to an everted proboscis was observed in one specimen (Ma- gelona cf. agoensis) and is herein described and discussed in relation to previous morphological studies.